Factors affecting pneumonia among children under five years old - Dewi, Indri Kurnia; Setiyawati, Nanik; Estiwidani, Dwiana (Jurnal Kesehatan Ibu dan Anak, 2019)
UNICEF mentioned that the main causes of under-five mortality are; pneumonia, diarrhea, malaria, and malnutrition. The incidence of pneumonia in children under-five in Indonesia in 2016 increased by 65.27% from the previous year. The purpose of this study was to find out the factors that influence the incidence of pneumonia in infants. The type of this study was analytical observational research with the case-control design used secondary data from medical records from January to December 2019 and primary data from direct interviews. The subject of this study were 94 toddlers with a purposive random sampling technique. Data analysis used a chi-square test followed by logistic regression. The results showed that pneumonia was most prevalent among children under five with risky toddlers (66.0%), history of non-risk birth weight (83.0%), toddlers who received exclusive breastfeeding (57.4%), toddlers who had received complete basic immunization (80.9%), mothers of children under five with basic education (63.8%), toddlers who had a family history of smoking (70.2%), parents (father/ mother) of toddlers who had a history of asthma (51, 1%), and toddlers who had received vitamin A (83.0%). Factors related to pneumonia in children under five were the age factor of the toddler (p-value: 0.038; 95% CI: 1.134-6.033), the last education of the mother (p-value: 0.002; 95% CI: 1.755-9,860), family smoking history (p-value: 0.036; 95% CI: 1,147-6,254), and a history of parent’s asthma (p-value: 0,000; 95% CI: 2,338-18,344). Age of toddler, mother's education level, family smoking history, and history of parental asthma were factors that influence the incidence of pneumonia in infants. The history of parent’s asthma was the most influential factor.